New optical features to enhance solar cell performance based on porous silicon surfaces - A., Ramizy; Z., Hassan; K., Omar; Y., Al-Douri; M.A., Mahdi (Elsevier B.V., 2011)
Link to publisher's homepage at www.elsevier.com/